Stimulating sulfur metabolism by overexpression of Sulfide:quinone reductase in Acidithiobacillus caldus coupled with low pH-high S0 integrated strategy in chalcocite bioleaching - Ruian Ji; Mingwei Wang; Xingyu Huo; Yiwen Zhu; Zhidong Guo; Yingming Wang; Jia Wang; Hailin Yang; Yanjun Tong; Shoushuai Feng (Bioresource Technology, 2026)

Multi-level metabolic engineering for efficient ergothioneine production in yeast using a Pleurotus ostreatus-derived pathway - Zhongjuan Di; Yanjun Huo; Yuejun Fu; Bo Li; Yingping Zhuang (Chemical Engineering Journal, 2026)

Accumulation pattern, source apportionment and risk assessment of soil heavy metals across diverse land use types: Insights from the northern foothills of Qinling mountains, China - Bingyao Huo; Yanjun Shen; Yibing Ning; Wei Shen; Penghui Ma; Zhijie Jia; Luqing Zhao; Junyan Zhao; Xing Chen; Tao Ding; Sirui Li; Jianbing Peng (CATENA, 2026)

Strong tri-genic epistasis among natural alleles of the OsMYB2–OsGH18–OsCAD3 module enhances drought tolerance in rice - Mingyue Huo; Shanwen Wang; Fan Zhang; Min Li; Ming Yin; Yuxin Lei; Yanfang Wang; Yanjun Chen; Dapu Liu; Xiuqin Zhao; Binying Fu; Fengyi Hu; et al. (Molecular Plant, 2026)

Arsenic exposure, genetic susceptibility, lifestyle, and glucose-insulin homeostasis impairment: Revealing the association and interaction in a repeated-measures prospective study - Yongfang Zhang; Jiahao Song; Ming Zhang; Gaoyin Xiong; Yanjun Guo; Wei Liu; Linling Yu; Quanhong Liu; Yueru Yang; Shuhui Wan; Qing Liu; Zhiying Huo; et al. (Environmental Research, 2025)

Transcriptional regulatory factor EpsR mediates adaptation mechanism of extremophile Acidithiobacillus caldus to copper stress environment and performance in bioleaching of low-grade copper ore by enhancing “contact” mechanism - Hongguang Xie; Xingyu Huo; Xiuwen Wang; Zhidong Guo; Yang Yuan; Hailin Yang; Yanjun Tong; Shoushuai Feng (Journal of Hazardous Materials, 2025)

Dual-template molecularly imprinted magnetic covalent organic framework for selective extraction of bisphenols - Shu-hui Huo; Mengya Qin; Xiaonan Zhang; Pengxin Zhou; Junhao Liu; Xiaoqiang Yao; Zhengang Han; Zhentong Zhu; Yanjun Feng; Zhilan Wang; Xiaoquan Lu (Chemical Engineering Journal, 2025)

LmCHS1 mediates pro-nymphal cuticle formation in Locusta migratoria embryogenesis - Yanjun Huo; Qing Dong; Xiaojian Liu; Jianzhen Zhang; Xueyao Zhang; Min Zhang; Tingting Zhang (Journal of Insect Physiology, 2025)

Enhancing acid resistance of Escherichia coli based on directed morphology evolutionary of key transcription factor bolA - Zongling Chen; Xingyu Huo; Jiali Wan; Jinming Che; Meiyi Deng; Yingnan Bao; Hailin Yang; Yanjun Tong; Shoushuai Feng (Food Bioscience, 2024)

Construction of low-resistance nano-transport channels with UiO-66-(NH2)2 “transmembrane” in polyamide layer structure for efficient nanofiltration - Xiaowen Huo; Yue Miao; Ziyang Guo; Zhiqiang Shi; Yanjun Jia; Haitao Wang; Na Chang (Chemical Engineering Journal, 2024)

Effect of use of NSAIDs or steroids during the acute phase of pain on the incidence of chronic pain: a systematic review and meta-analysis of randomised trials - Luyao Huo; Gang Liu; Bowen Deng; Lin Xu; Yanjun Mo; Shengyuan Jiang; Jingwei Tao; Huizhong Bai; Li Wang; Xiaoxiao Yang; Jizhou Yang; Xiaohong Mu (Inflammopharmacology, 2024)
Background This study is the first to summarize the evidence on how the use of anti-inflammatory drugs during acute pain has an impact on the development of chronic pain. Methods Randomized controlled trials retrieved from nine databases included anti-inflammatory drugs (NSAIDs or steroids) versus non-anti-inflammatory drugs in patients with acute pain and reported the incidence of chronic pain. No specified date, age, sex, or language restrictions. Subgroup analyses were performed according to pain classification, follow-up time, and medication. The GRADE method was used to evaluate quality of evidence. Results A total of 29 trials (5220 patients) were included. Steroids or NSAIDs did not reduce the incidence of chronic nociceptive pain. Steroid use in acute phase significantly reduced the incidence of chronic neuropathic pain. In subgroup analysis, benefits were observed for methylprednisolone and dexamethasone, with some adverse effects. Steroids or NSAIDs were statistically significant in reducing pain intensity over 1 year, but the effect size was too small, and whether the long-term effect is clinically relevant needs to be further studied. Conclusion Quality of the evidence was low to moderate. No drug can be recommended to prevent chronic nociceptive pain. Injections of steroids (methylprednisolone or dexamethasone) during the acute phase reduce the incidence of chronic neuropathic pain, but most included studies also used local anesthetics. The results are indirect and need to be interpreted with caution. The pooled data effect sizes for pain intensity were small, so the clinical relevance was unclear. Study registration PROSPERO (CRD42022367030).

Tetramethylpyrazine inhibits the inflammatory response by downregulating the TNFR1/IκB-α/NF-κB p65 pathway after spinal cord injury - Gang Liu; Luyao Huo; Bowen Deng; Shengyuan Jiang; Yi Zhao; Yanjun Mo; Huizhong Bai; Lin Xu; Chuanyu Hu; Xiaohong Mu (Toxicology and Applied Pharmacology, 2024)

Enhancing column bioleaching of chalcocite by isolated iron metabolism partners Leptospirillum ferriphilum/Acidiphilium sp. coupling with systematically utilizing cellulosic waste - Xingyu Huo; Jianna Liu; Xianjing Hong; Haochen Bai; Zongling Chen; Jinming Che; Hailin Yang; Yanjun Tong; Shoushuai Feng (Bioresource Technology, 2024)

Associations between congenital heart disease and air pollutants at different gestational weeks: a time-series analysis - Wenling Zhang; Yanjun Yang; Yanyan Liu; Li Zhou; Yan Yang; Li Pan; Yupei Ba; Ruijuan Wang; Yanbei Huo; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Geochemistry and Health, 2023)

Association between air pollutants and neural tube defects during pregnancy in Lanzhou, China: a time series analysis - Yan Yang; Li Zhou; Wenling Zhang; Yanjun Yang; Yanyan Liu; Li Pan; Yanbei Huo; Ruijuan Wang; Yupei Ba; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Science and Pollution Research, 2023)

Time series analysis on association between ambient air pollutants and orofacial clefts during pregnancy in Lanzhou, China - Yanyan Liu; Li Zhou; Wenling Zhang; Yanjun Yang; Yan Yang; Li Pan; Yupei Ba; Ruijuan Wang; Yanbei Huo; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Science and Pollution Research, 2022)

Mechanical Properties of Acid-corroded Sandstone Under Uniaxial Compression - Shuguang Li; Yingming Wu; Runke Huo; Zhanping Song; Yoshiaki Fujii; Yanjun Shen (Rock Mechanics and Rock Engineering, 2021)